TRAINING OF TRAINERS FOR KADER SURABAYA HEBAT (KSH) IN RATIONAL ANTIBIOTIC USE FOR DENTISTRY AT PUSKESMAS PEGIRIAN - Fauziah, Yessy Andriani; Darmadi, Eveline Yulia; Widjaja, Jennifer; Ameliana, Yemy; Ritunga, Imelda (LPPM Univ. Ibn Khaldun Bogor, 2025)
The irrational use of antibiotics in dentistry, including self-medication, incomplete treatment, and inappropriate prescriptions, remains a major public health concern that contributes to antimicrobial resistance. At the same time, many communities lack sufficient access to accurate information on the proper use of antibiotics in dental care. Situation analysis at Puskesmas Pegirian highlighted that Kader Surabaya Hebat (KSH) play a central role in health promotion but require greater knowledge and confidence to educate the public on rational antibiotic practices. To address this gap, a Training of Trainers program was designed and implemented with KSH as participants. The training combined health counseling sessions, interactive discussions, and practical demonstrations focused on the importance of rational antibiotic use in dentistry. To evaluate the effectiveness of the program, participants completed a pre-test before the training and a post-test after the sessions. The results showed a clear improvement in knowledge and awareness, with KSH reporting stronger confidence to deliver educational messages within their communities. This initiative demonstrates that targeted training supported by measurable evaluation can effectively strengthen the role of KSH. The conclusion emphasizes that investing in KSH capacity is a sustainable strategy to promote rational antibiotic use in dentistry at the community level.